The Effectiveness of Learning in the Islamic Education Laboratory in Cultivating Islamic Values in Schools - Sulastini, Tanti (Lembaga Penelitian dan Pendidikan Mandala, 2025)
Islamic education in schools plays a crucial role in shaping students' character and Islamic values, and Islamic education laboratories can be an effective means of achieving this goal. These laboratories are not merely physical spaces, but also learning environments designed to facilitate direct experience and application of Islamic values in practical contexts. This article aims to analyze the effectiveness of Islamic education laboratories in fostering Islamic values in the school environment, exploring how these laboratories can be important instruments in the internalization of values such as piety, honesty, tolerance, and responsibility. The research methods used include literature review and descriptive analysis. Through a series of activities and facilities provided, students are given the opportunity to deeply explore, internalize, and practice Islamic teachings. Strengthening religious-based character education can improve school quality.